Mechanisms in surface coloring of titanium alloy induced by picosecond laser. (April 2022) - Huang, Yandi; Zhang, Chunyu; Zhang, Chenchu; Li, Guo; Chen, Qianjun; Song, Chengwei
Abstract: Various colors can be obtained on the surface of Ti-6Al-4V (TC4) alloy through picosecond pulsed laser scanning under different laser parameters, which can be expressed by the standard CMYK (cyan-magenta-yellow-black) color mode. In this paper, the microstructure and chemical components of the colored parts were investigated by scanning electron microscope (SEM) and energy dispersive spectroscopy (EDS). Combined with the observation of the optical microscope images, it is found that the color is produced by the oxide layer formed on the surface of TC4. In addition, the color rendering results are affected by the resolution of human eyes, laser-induced surface microstructure and proportion of different color patches. Furthermore, the relationships between laser energy, machining parameter and coloring results were qualitatively investigated, and the limiting effect of hue on saturation was clearly stated. Under the premise of appropriate laser energy, complex paintings have been successfully produced on TC4 alloy surfaces by change scanning speed and line spacing. This study offers a new approach to produce diverse colors on TC4 alloy, which may find a wide range of applications in the laser color marking. Graphical abstract: Picosecond laser coloring processing of complex images on TC4 alloys. Unlabelled Image Highlights: Colorization on Ti-6Al-4V was realized via picosecond laser manufacture. A coloring mechanism with the effect of oxidation, microstructure and human eye resolution was proposed. The influence of laser parameters on colors were quantitatively investigated. Complicated paintings were processed on TC4 planes.